2004
DOI: 10.1074/jbc.m400641200
|View full text |Cite
|
Sign up to set email alerts
|

Nodal and ALK7 Inhibit Proliferation and Induce Apoptosis in Human Trophoblast Cells

Abstract: Nodal, a member of the transforming growth factor-␤ superfamily, is known to play critical roles in early vertebrate development, but its functions in extraembryonic tissues are unclear. ALK7 is a type I receptor for Nodal. Recently, we demonstrated that Nodal mRNA and several ALK7 transcripts are expressed in human placenta throughout pregnancy (Roberts, H. J., Hu, S., Qiu, Q., Leung, P. C. K., Cannigia, I., Gruslin, A., Tsang, B., and Peng, C. (2003) Biol. Reprod. 68, 1719 -1726). In this study, we determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 46 publications
8
64
0
Order By: Relevance
“…ALK7 influences cell proliferation and induces cell apoptosis and these effects have been found in a rat neuronal cell line, hepatoma cells, human trophoblast cells and ovarian cancer cells (12,(14)(15)(16)19). We also found a similar phenomenon in breast cancer cell lines MDA-MB-231 and MCF-7 and this was consistent with the result from a study on ZR-75-30 breast cancer cell (17).…”
Section: Cytotoxicity Assays Of Mcf-7 Activin Receptor-like Kinase supporting
confidence: 81%
See 2 more Smart Citations
“…ALK7 influences cell proliferation and induces cell apoptosis and these effects have been found in a rat neuronal cell line, hepatoma cells, human trophoblast cells and ovarian cancer cells (12,(14)(15)(16)19). We also found a similar phenomenon in breast cancer cell lines MDA-MB-231 and MCF-7 and this was consistent with the result from a study on ZR-75-30 breast cancer cell (17).…”
Section: Cytotoxicity Assays Of Mcf-7 Activin Receptor-like Kinase supporting
confidence: 81%
“…In addition, constitutively activated ALK7 induces apoptosis of hepatoma and pancreatic β cells (12,13). Nodal acts via ALK7 to inhibit proliferation and induce apoptosis of human trophoblast cells (14), and epithelial ovarian cancer cells (15,16). These findings support the role of nodal-ALK7 pathway in mediating cell proliferation and apoptosis of cancer cells.…”
Section: Abstract Aim: To Examine the Expression And Function Of Actsupporting
confidence: 68%
See 1 more Smart Citation
“…It is known, for example, that Nodal signalling can maintain pluripotency and prevent differentiation to neuroectoderm in human embryonic stem cells (hESC) and mouse epiblastderived stems cells (mEpiSC) [32] while it is necessary for endoderm differentiation in pluripotent cells and the mouse gastrula embryo [3,33]. Similarly, Nodal can inhibit cell migration, invasion and proliferation in human trophoblasts [34,35] while it promotes the opposite in human glioma and breast cancer cells [36,37]. Such divergent mechanisms create the necessity of developing a conceptual framework to help recognize L-R patterns and assess the phenomenon in a meaningful manner.…”
Section: Context-dependency Of Nodal Functions In Nervous System Asymmentioning
confidence: 99%
“…Our results showed that both blood pressure and LVMI were associated with rs13010956, suggesting a potential role of the ALK7 gene polymorphism in the early stages of diastolic heart failure. Previous studies have revealed the significance of ALK7 in cell apoptosis and proliferation 13,27,28 . However, whether the ALK7 gene polymorphism contributes to cardiac remodeling and heart dysfunction by playing a role in myocardial apoptosis and fibrosis needs to be determined in the future.…”
Section: Discussionmentioning
confidence: 99%